Vineyard light manipulation and silicon enhance ethylene-induced anthocyanin accumulation in red table grapes - Afifi, Maha; Rezk, Alaaeldin; Obenland, David; El-kereamy, Ashraf (Frontiers in Plant Science, 2023)
Red color, produced by anthocyanin pigment, is an essential trait for premium table grape production. Anthocyanin synthesis occurs through the flavonoid pathway which includes several enzymatic reactions coded by different genes. The expression of these genes is regulated by different cultural practices, environmental conditions, and plant hormones. Recently, we reported that the anthocyanin pathway is regulated by several factors such as light and antioxidant activity. Despite the advances in cultural practices, it is still challenging to produce table grapes with high coloration, especially under the current and expected global climate change in warmer areas such as California. In the current study, we deployed two approaches to improve the accumulation of red pigment in table grapes. The first approach involves improving the expression of critical genes involved in the anthocyanin pathway through hormonal treatments and light manipulation using a reflective ground cover (RGC). The second approach was to reduce the negative effect of heat stress through stimulation of the antioxidant pathway to help remove free radicals. Treatments included ethephon (ET) at 600 mg/L, silicon (Si) at 175 mg/L, and a commercial light-reflective white ground cover (RGC) alone and in various combinations. Treatments were conducted either with or without a combination of cluster-zone leaf removal at veraison (LR) on Flame seedless (Vitis vinifera L.). Data collected in 2018 and 2019 showed that the best treatment to improve berry coloration was using ET in combination with Si and RGC, applied at veraison. Adding the LR to this combination did not improve berry color any further, but rather caused a reduction in color development. RGC without conducting LR at veraison significantly increased the quantity of reflected blue and red lights as well as the red (R) to far-red (FR) ratio (R: FR) around clusters. Results were in accordance with the increase in gene expression of flavonoid-3-O-glucosyltransferase (UFGT), a key gene in the anthocyanin biosynthesis pathway, as well as Peroxidase dismutase (POD). Manipulating the light spectrum and application of silicon in combination with the ethephon treatment could be used in table grape vineyards to improve the ethylene-induced anthocyanin accumulation and coloration.